Achieving Project Management Educational Web-Tool Evolution Using Service-based Software - Araújo, Thiago; Neves, Raul; Dias, Matheus; Muller, Dionas; Bernardino, Maicon (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2024)
Project Management (PM) is vital in software development and the availability of educational tools enhances the learning experience of best practices. This study focuses on developing a web-tool for PM education and employed a service-based software approach to develop a web-tool. We conducted a survey using the LimeSurvey platform to identify PMBOK® aspects to define technical requirements, gather user input for the tool’s new version, and formulate research questions to guide implementation. Survey results from 16 respondents revealed knowledge areas with insufficient PMBOK® coverage and areas needing non-functional improvements. The questionnaire design and administration adhered to best practices, offering valuable insights for tool development. This study emphasizes the significance of PM education and the need for effective tools. The developed web-tool aids students and professors in adhering to best practices and enhancing PM skills. Future research can focus on further enhancing the tool and evaluating its effectiveness in educational settings.